Avaliação de espécies migradoras de peixes e do ictioplâncton no rio Pandeiros, Minas Gerais - Bueno, Marina Lopes (2016)
In order to obtain information about the migratory species and ichthyoplankton dynamics in the Pandeiros river, important tributary of the São Francisco river, the aim of this study was to evaluate the distribution of migratory species and the role of the Pandeiros Small Hydro Power (SHP) in this distribution. For this purpose, we evaluated the use of the river as a spawning site, identifying the main breeding and early development sites, as well as the benefits of a possible dam decommissioning on these populations. Fishes were collected with gillnets with mesh ranging from 3-16 cm between opposites knots, between July 2014 and February 2016. For the ichthyoplankton sampling, five monthly samplings were performed in the rainy season, from November 2014 to March 2015. Eight sampling sites were established, matched to both types of sampling. A total of 2705 fishes was collected, belonging to 67 species, nine of which were migratory species. Migratory species were recorded in all downstream points of the SHP. In contrast, in the upstream of the SHP, these species were collected only in two points. The ichthyoplankton density was also higher downstream. The flow was the only abiotic factor that was positively correlated to the density of eggs and, consequently, to fish reproduction. The results of this study provided evidence that the Pandeiros SHP is negatively influencing the migratory dynamics and the fish reproduction in the Pandeiros river. Therefore, the decommissioning could generate positive effects on local ichthyofauna.